APPLICATION OF ACTIVITY BASED COSTING AS THE BASIS FOR DETERMINATION OF TARIFF IN PATIENT HOSPITAL IN PROF.DR.R D. KANDOU MANADO - Makal, Verra Sherly; Nangoi, Grace B. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The viability of the institution of which is determined by a variety of strategies implemented by ABC, an accounting information system to identify kinds of activities undertaken and collect fees on the basis of existing nature of the activity. Prof. Kandou general hospital Manado becomes the object of study, located in the city of Manado. The study was conducted by calculating the room rates of hospitalization on the basis of unit cost separately for each type of class hospitalization. The aim of this research is to find out the ABC application as a basis for setting rates of inpatient services at the hospital Prof. Kandou Manado. The research is descriptive, namely from the calculation of rates of hospitalization by using the ABC system. When compared with hospitalization rates that are used by hospitals today, it appears that the rate of hospitalization for class I, II, III gives smaller yield, with a difference of Rp. 190,546.5 VVIP class, class VIP 94241.3, class I -65,086.4 class II Rp Rp Rp -208,605.9 -161,232.5 class III. While VVIP, VIP, providing greater results. The management of Prof. Kandou hospital should consider the implementation of hospitalization rates by using the ABC because this system will obtain information of hospitalization costs more accurately. Keywords: fee based activities, tariffs